Hospital Characteristics, Inpatient Processes of Care, and Readmissions of Older Adults with Hip Fractures. Issue 8 (28th June 2016) - Elkassabany, Nabil M.; Passarella, Molly; Mehta, Samir; Liu, Jiabin; Neuman, Mark D.
Abstract : Objectives: To determine hospital‐level predictors of readmission after hip fracture or potentially related inpatient care processes. Design: Retrospective cohort study. Setting: U.S. acute care hospitals. Participants: Fee‐for‐service Medicare beneficiaries who underwent hip fracture surgery between 2007 and 2009 (N = 458, 526). Measurements: Information was obtained on hospital case volumes, teaching status, bed count, nurse staffing, and technological capabilities from Medicare files, and multivariable logistic regression was used to measure the association between these factors and an endpoint of readmission or death at 30 days and between these factors and the timing of surgery. Results: Participants treated in the highest‐volume hospitals (>175 cases for the study period) had lower odds of readmission or death at 30 days than those treated in low‐volume hospitals (≤12; adjusted odds ratio (aOR) = 0.87, 95% confidence interval (CI) = 0.83–0.92, P < .001). Higher nurse skill mix (aOR = 0.88, 95% CI = 0.8–0.96; P = .007) and higher ratio of nurses to beds (aOR = 0.98; 95% CI = 0.97–0.99; P < .001) were also associated with better 30‐day outcomes. Greater hospital case volume was associated with lower odds of surgical delay beyond 48 hours. Conclusion: Better nurse staffing and higher case volumes are associated with lower rates of readmission and mortality after hip fracture surgery; individuals treated at high‐volume centers experienced fewer delays in treatment, potentially indicating better inpatient care processes.